Walter Scott's Late Gothic Stories. Issue 1 (March 2021) - Cook, Daniel
Abstract : While 'Wandering Willie's Tale', above all of Walter Scott's shorter fictions, has often been included in Gothic anthologies and period surveys, the apparently disposable pieces that appeared in The Keepsake for 1829, renegades from the novelist's failed Chronicles of the Canongate series, have received far less attention. Read in the unlikely context of a plush Christmas gift book, 'My Aunt Margaret's Mirror' and 'The Tapestried Chamber' repay an audience familiar with the conventions of a supernatural short story. But to keep readers interested, The Author of Waverley, writing at the end of a long and celebrated career in fiction, would need to employ some new gimmicks. As we shall see, the late stories are not literary cast-offs but recastings finely attuned to a bespoke word-and-image forum.